Historical dictionary of the U.S. presidency - Conley, Richard Steven (Historical dictionaries of U.S. politics and political eras, 2016)
This book covers the development of the presidential office within the context of constitutional interpretations of presidential power and sociopolitical and economic developments, as well as foreign affairs events, from 1789-2015. It provides details on the men who have held the office, and biographies of vice presidents, unsuccessful candidates for the office, and noteworthy Supreme Court and other appointees. The Historical Dictionary of the U.S. Presidency contains a chronology, an introduction, appendixes, and an extensive bibliography. The dictionary section has over 300 cross-referenced entries on the development of the institution of the presidency, and details the personalities, domestic and foreign policy governing contexts, elections, party dynamics and significant events that have shaped the office from the Founding to the present day. This book is an excellent resource for students, researchers, and anyone wanting to know more about the U.S. Presidency.